Transcriptome analysis reveals in vitro cultured Withania somnifera leaf and root tissues as a promising source for targeted withanolide biosynthesis - Senthil, Kalaiselvi (BMC Genomics, 2015)
BACKGROUND: The production of metabolites via in vitro culture is promoted by the availability of fully defined metabolic pathways. Withanolides, the major bioactive phytochemicals of Withania somnifera, have been well studied for their pharmacological activities. However, only a few attempts have been made to identify key candidate genes involved in withanolide biosynthesis. Understanding the steps involved in withanolide biosynthesis is essential for metabolic engineering of this plant to increase withanolide production. RESULTS: Transcriptome sequencing was performed on in vitro adventitious root and leaf tissues using the Illumina platform. We obtained a total of 177,156 assembled transcripts with an average unigene length of 1,033 bp. About 13% of the transcripts were unique to in vitro adventitious roots but no unique transcripts were observed in in vitro-grown leaves. A putative withanolide biosynthetic pathway was deduced by mapping the assembled transcripts to the KEGG database, and the expression of candidate withanolide biosynthesis genes -were validated by qRT PCR. The accumulation pattern of withaferin A and withanolide A varied according to the type of tissue and the culture period. Further, we demonstrated that in vitro leaf extracts exhibit anticancer activity against human gastric adenocarcinoma cell lines at sub G1 phase. CONCLUSIONS: We report here a validated large-scale transcriptome data set and the potential biological activity of in vitro cultures of W. somnifera. This study provides important information to enhance tissue-specific expression and accumulation of secondary metabolites, paving the way for industrialization of in vitro cultures of W. somnifera. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-015-1214-0) contains supplementary material, which is available to authorized users.